PENERAPAN KARAKTER WASAKA DALAM MENINGKATKAN KECERDASAN ADVERSITAS - Miftahul Aula Sa’adah; Hamdan Juwaeni (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research aims to explore how the application of Wasaka characters in improving adversity intelligence. Adversity intelligence refers to a student's ability to face, overcome, and thrive despite difficulties and pressures. This research uses a type of field research with a qualitative descriptive approach. The subjects in the study were the principal, teachers and students at MtsN 1 Banjar. Data was collected through in-depth interviews. After the data was collected, it was analyzed using inductive techniques that took steps: data reduction, data presentation, and data verification. The results showed that MtsN 1 Banjar has implemented Wasaka character through learning tools that are integrated in subject areas. Making lesson plans includes the content of character education and the implementation of Wasaka characters in the learning process and extracurricular activities